Analysing The Impact Of Quantitative Easing Policy - Touati Tliba ,Nacima; Gharbi, Hicham (جامعة الوادي University of Eloued, 2024)
This study aims to examine the relationship between the Federal Reserve's Quantitative Easing policy and US sovereign debt valuation, focusing on the period from 1990 to 2022. Using a Vector Autoregressive (VAR) model, we analysed the dynamic interactions between key economic variables, including Treasury yields, QE amounts, GDP, inflation rates, and Federal Funds rates. The quantitative easing policies pursued by the US Federal Reserve have led to increased scrutiny of the debts of countries issuing reserve currencies. The US sovereign debt was significantly affected by these policies, but there has not been much work on the direct dynamics between QE policy and the value of sovereign debt for the US market. The study strives to contribute to the literature by estimating the US sovereign debt valuation reaction to changes in the balance sheet caused by the quantitative easing policy. Valuation of US sovereign debts is an important issue due to the influential role of US sovereign bonds in diverse international financial markets. Our findings indicate that large-scale asset purchases cause changes in U.S. sovereign debt bond prices and their valuation.
Analysing the Impact of Quantitative Easing Policy on US Sovereign Debt Valuation: Using A VAR Model during the period 1990 2022
Keywords: Quantitative Easing policy; US sovereign debt; Vector Autoregressive (VAR) model; Treasury yields; QE amounts.